2021
DOI: 10.1002/ejoc.202100883
|View full text |Cite
|
Sign up to set email alerts
|

Borane Catalyzed Redox Isomerization of 2‐Amino Chalcones: Hydride Abstraction or Hydride Migration?

Abstract: The borane catalyzed redox isomerization of 2-amino chalcones was developed. The tetrahydroquinolines are obtained in high yield as a mixture of cis/trans diastereomers in a ratio of 2 : 1 to > 95 : 5. The reaction mechanism is investigated by mechanistic, kinetic, and computational methods, concluding that the reaction proceeds through concerted [1,5] hydride shift in contrast to borane-mediated C(sp 3 )À H hydride abstraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…These observations suggested that a [1,5]-hydride shift process was involved in the reaction and excluded the hydride abstraction mediated by the borane. 15 A crossover experiment using 4a and 4a-[D6] was performed then in a shortened reaction time ( Scheme 4c ). At low conversions, a significant kinetic isotope effect (KIE) of 3.0 was observed, revealing that the [1,5]-hydride transfer could be involved in the rate-determining step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggested that a [1,5]-hydride shift process was involved in the reaction and excluded the hydride abstraction mediated by the borane. 15 A crossover experiment using 4a and 4a-[D6] was performed then in a shortened reaction time ( Scheme 4c ). At low conversions, a significant kinetic isotope effect (KIE) of 3.0 was observed, revealing that the [1,5]-hydride transfer could be involved in the rate-determining step.…”
Section: Resultsmentioning
confidence: 99%
“… 11–14 In particular, B(C 6 F 5 ) 3 -catalyzed intramolecular cyclization of ortho -substituted N , N -dialkyl arylamines via hydride transfer to afford tetrahydroquinoline derivatives was realized by the Paradies group and Wang group, respectively. 15,16 Nevertheless, the synthesis of tetrahydroquinolines through B(C 6 F 5 ) 3 -catalyzed intermolecular redox-neutral annulation still remains elusive in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…We envisioned utilization of the C(sp 3 )−H activation to generate an electrophilic iminium ion and transfer the hydride to a Michael position in order to obtain an enolate and consequently trigger a Mannich-type reaction for intramolecular C−C bond formation. However, we found that in our systems, the activation of the α,βunsaturated ketones 48a−g initiates a [1,5] hydride shift that resulted in the tetrahydroquinolines 49a−g in high yields (Scheme 13), 61 also known as the tert-amino effect. 62 Kinetic, isotope labeling, and control experiments provided support that the reaction proceeds through the direct [1,5] hydride transfer to the activated Michael position and not through the hydride abstraction mechanism.…”
Section: Flp-catalyzed Reactionsmentioning
confidence: 77%
“…On the other side, the Lewis acidity of the triaryl borane required adjustment, because compared to an imine, the imidoyl chloride is significantly less Lewis basic and must be thus counterbalanced. These challenges were overcome with the use of tris(1-naphthyl)phosphine oxide (61), which turned out to have the best balance between deoxygenation rate and compatibility with the slightly more Lewis acidic borane B(2,3,6-F 3 −C 6 H 2 ) 3 (62). The substrate scope of the FLP-catalyzed reductive deoxygenation of the secondary amides 63a−l is comparable to that of the reduction of tertiary amides (Scheme 20b).…”
Section: Flp-catalyzed Reductive Deoxygenationsmentioning
confidence: 99%
See 1 more Smart Citation